Abuses of the erotic : militarizing sexuality in the post-Cold War United States - Cerretti, Josh (Expanding frontiers., 2019)
Events ranging from sexual abuse at Abu Ghraib to the end of "Don't Ask, Don't Tell" hint that important issues surrounding gender and sexuality remain at the core of political and cultural problems. Nonetheless, intersectional analyses of militarism that account for questions of race, class, and gender remain exceedingly rare. This book fills this gap by offering a comprehensive picture of how military values have permeated the civilian cultural sphere and by investigating connections between sexuality and militarism in the United States since the late 1980s. The author takes up the urgent task of applying an interdisciplinary, transnational framework to the role of sexuality in promoting, expanding, and sustaining the war on terror to understand the links between what the author calls "domestic militarism" and later projects of state-backed violence and intervention. This work brings together scholarship on domestic and international militarization in relation to both homosexuality and heterosexuality to demonstrate how sexual and gender politics have been deployed to bolster U.S. military policies and, by tracking over a decade of militarized sexuality, how these instances have foundationally changed how we think of sexual and gender politics today